Um método para análise de faltas em sistemas de energia com geradores distribuídos conectados à rede por meio de conversores de frequência completos - Lemos, Herick Talles Queiroz (Universidade Federal Rural do Semi-Árido, 2019)
The study of electrical systems under fault conditions provides fundamental information for the design and configuration of the network protection. These studies are traditionally performed in the phasor domain and based on the physical behavior of the synchronous generators directly connected to the network. However, the increase of full-scale converter-based (FSC – based) distributed generators connections to the grid has created the need for new short-circuit analysis methods, since, unlike the synchronous generators, the converter current contribution depends only on its pre-fault control strategy and the applied Fault Ride Through – FRT requirements. In this work, an improved fault analysis method is proposed to assess the current contribution of FSC-based distributed generators to different pre-fault control strategies and FRT requirements using accessible data to planning engineers. In the proposed method the converter was modeled as a voltage controlled current source that injects only positive sequence currents with magnitude and phase angles dependent on the pre-fault control strategy, maximum converter specifications, and FRT requirements. In this work were developed algorithms for modeling the pre-fault control strategies Constant Power Factor - FPC, Constant Voltage – VC and Constant Reactive Power – QC, and an algorithm for grid voltage support requirement of the Brazilian grid code. The converter current source model is subsequently converted to an impedance equivalent and included in a classical fault analysis method based on the bus impedance matrix. The proposed algorithms were demonstrated in study cases and later validated by comparing the obtained results with the professional software Simultaneous Fault Analysis - ANAFAS. For all evaluated faults, the proposed algorithms presented an excellent performance in the estimation of the steady-state current contribution from converters, which shows that they can be implemented in any commercial software of power system analysis
Keywords: Curtos-circuitos; Geração distribuída; Conversor de frequências completo; Short-circuits; Distributed generarion; Full scale converters; ENGENHARIAS::ENGENHARIA ELETRICA